Benefit-Risk Evaluation and Decision Making: Some Practical Insights. (May 2015) - Colopy, Michael W.; Damaraju, C. V.; He, Weili; Jiang, Qi; Levitan, Bennett S.; Ruan, Shiling; Yuan, Zhong
Pharmaceutical drugs and devices are increasingly evaluated by quantitative tools that combine benefit and risk. These tools vary by their limitations and desirable properties, which may confuse the decision-making process. Experts from the Food and Drug Administration (FDA) and industry shared their perspectives at the 2012 American Statistical Association (ASA) Biopharmaceutical Section FDA-Industry Statistics Workshop, and these insights are presented here. First, benefit-risk terminology is given to better understand subtle distinctions. Next, pragmatic considerations in endpoint selection are given that distinguish between benefit-risk assessment and analysis of clinical trials. Then the strengths of weighting methods, including ranking, utilities, and risk tolerance for assessing the trade-off between benefits and risks, are compared. The last topic presented is summarizing information to ease the interpretation, transparency, and ability to support decisions. Benefit-risk methods are moving towards a unified paradigm to make selection of endpoints, weights, and metrics easier and more structured. This will lead to better decision-making based on a transparent assessment and clear interpretability.